Discordance between patient self-report and clinician record of adverse drug reactions to drug-resistant Tuberculosis Treatment in Johannesburg, 2015 – 2018 - Iniobong, Unyime (My University, 2022)
Background Drug-resistant tuberculosis (DR-TB) is a threat to global tuberculosis prevention and control. Treatment is also complicated by adverse drug reactions (ADRs) to the second-line TB drugs. However, there is a lack of data on the discordance between patient self-report and clinician record of ADRs during DR-TB treatment, which may impact treatment outcomes such as adherence or retention in care. This study's objectives were to describe patient self-report and clinician record of ADRs during DR-TB treatment and the degree of the concordance between the two. This study also aimed to determine the relationship between a missed clinician record of ADRs and poor clinic attendance. Methods This was a cross-sectional study of adults with laboratory-confirmed rifampicin resistant tuberculosis (TB) on DR-TB treatment at a public-sector outpatient DR-TB clinic in Johannesburg, South Africa between 02/2015–01/2018. The first was a secondary analysis of data that was collected to describe the quality of life and self-reported adverse events among patients on RR-/MDR-TB treatment at Helen Joseph Hospital, Johannesburg, South Africa. The second, a medical record review to collect data on ADRs reported for the patients included in the aforementioned study sample. A descriptive analysis was performed to describe patient self-report and clinician record of ADRs during DR-TB treatment disaggregated by patient demographic and clinical characteristics. To determine the degree of discordance between patient self-report and clinician record of ADRs to DR-TB treatment, Cohen’s Kappa statistics (K), Gwet’s Agreement coefficient with first order chance correction (ACI) and McNemar tests were used. The relationship between a missed clinician record of any ADRs and the likelihood of missing a clinic appointment (within 3 months of the visit date) was determined using a multivariate logistic regression. Results Results from patient self-report of ADRs showed that 38.9% (58/149) reported a total of 122 ADRs while the clinician record of ADRs showed that 67.1% (100/149) reported a total of 141 ADRs. Kappa’s scores ranged from -0.01 (poor) to 0.49 (moderate), ACI scores ranged from 0.39 to 0.99, percentage agreement ranged from 62% to 99%. Patient self-report and clinician report were more likely to be discordant when the ADR reported was a sign or symptom (i.e., rash, vomiting, nausea or joint pain), compared to when the ADR reported was a clinical diagnosis (i.e., hearing loss, peripheral neuropathy, psychosis or anaemia). A missed clinician record of any ADRs was not associated with missing a clinic appointment in 3 months following the visit date. On the contrary, where a clinician missed a record of any ADRs patients appeared less likely to miss their subsequent clinic appointment (51.9 % versus 65.1%; aOR 0.43 95% CI 0.13 – 1.34; p=0.148). Discussions and Conclusions The incidence of ADRs obtained from the clinician record was higher than that from patient self-report. Clinician record of ADRs is often objective and based on laboratory results (e.g., haemoglobin for anaemia, alanine transaminase for liver toxicity, or serum creatinine for kidney toxicity) or investigations like audiometry. In contrast, patient self-report of ADR is subjective and based on patient knowledge, understanding, and recall of their experience. Gaps between clinician and patient report of ADRs suggest an opportunity to improve reporting of ADRs by clinicians and improve patient counseling about ADRs related to DRTB treatment so that patients can recognize ADRs and communicate this information to clinicians during consultations. Improvements in reporting ADRs and appropriate management can result in improved DR-TB treatment outcomes. Early detection, prompt management, and pharmacovigilance reporting of ADRs remain vital factors in managing RR/MDR-TB.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology (Epidemiology and Biostatistics) to the Faculty of Health Sciences, School of Public Health, University of Witwatersrand, Johannesburg, 2022